PERAN EKSTRAKURIKULER BELA DIRI SILAMBAWIQRI DALAM MENERAPKAN NILAI KARAKTER KEBANGSAAN - Ridho Nuryani; Damanhuri Damanhuri; Dinar Sugiana Fitrayadi (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2023)
Abstract This study aims to find out 1) How to foster national character values ​​in students through the Silambawiqri extracurricular 2) What is the role of the Silambawiqri extracurricular in preventing delinquency adolescents and the negative influence of foreign culture on students at Madrasah Aliyah Negeri 1 Serang City 3) What obstacles and challenges are faced in the Silambawiqri extracurricular activities at Madrasah Aliyah Negeri 1 Serang City. The method used in this research is descriptive method with a qualitative approach. The results of the study show that the way to cultivate national character values ​​in students through the Silambawiqri extracurricular is the application of seven national character values, namely: religious values, discipline, responsibility, respect for achievement, national spirit, hard work and creativity. It can be concluded that the role of the Silambawiqri extracurricular in minimizing juvenile delinquency at Madrasah Aliyah Negeri 1 Serang City can be concluded that it has enough roles by paying attention to several aspects, namely the good adaptability of students, the Lalubawiqri extracurricular has also become a place for students who have an interest in local arts and culture and self-defense. In addition, students are also considered to have a high social sense. The challenges and obstacles that occur in Silambawiqri extracurricular activities at Madrasah Aliyah Negeri 1 City of Serang are time management and availability of training equipment needs.